Oxidation of AISI 304L and 348 Stainless Steels in Water at High Temperatures - Avelar,Alan Matias (2020)
Oxidation of AISI 304L and 348 stainless steels was investigated in water at 1000 – 1350 °C by TGA, SEM, EDS, and Raman spectroscopy. Linear-Parabolic kinetics and multilayer oxide scales with voids were found for both alloys. Based on the experimental results, AISI 304L presented higher oxidation resistance and higher activation energy. Zircaloy-4 kinetic results were used for validation and performance comparison. In severe accidents conditions, stainless steel might lead to a faster hydrogen production comparing to Zircaloy.